If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11f = 7(1 + -2f + 5) Reorder the terms: -11f = 7(1 + 5 + -2f) Combine like terms: 1 + 5 = 6 -11f = 7(6 + -2f) -11f = (6 * 7 + -2f * 7) -11f = (42 + -14f) Solving -11f = 42 + -14f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '14f' to each side of the equation. -11f + 14f = 42 + -14f + 14f Combine like terms: -11f + 14f = 3f 3f = 42 + -14f + 14f Combine like terms: -14f + 14f = 0 3f = 42 + 0 3f = 42 Divide each side by '3'. f = 14 Simplifying f = 14
| 6-3=5 | | 3y^3+2x^4y=7 | | -12g-9g-3=18 | | 2x^2+9x+41=0 | | x+y=4x-y+2 | | 5x-60=2x+3 | | w*4w=96 | | (5x+4)=16 | | v1/2=2 | | 6(x-1)-2x=3(x+1)+x | | 19w-10w-5=13 | | (2x+5)=(8x-5) | | 5(n-2)-3(2n+1)=4(1+n) | | 2x^2+5x-41=0 | | 20-14z=-20z-20+16 | | 2x^2+5-41=0 | | 15x/16=1/8 | | 15x/16 | | -18.53+11.6s-9.09=16.1s+6.58 | | -7c-5=-7c^2-3c+8 | | 7x+5y+1=0 | | -2(m-13)+-5=-9 | | 5*8(2*9)/4 | | -(8x+12)=(3x-(-13)) | | 3q-15=9+5q | | (X/7)=-4 | | f(-20)=0.25x+260 | | 12w-10w-2=14 | | Y=(1/2)^2-1/2-42 | | 5*sin(x)=3-cos(2x) | | -16u+11u+10=-20 | | 1.8n=0.5n-11.44 |